Literary Review on Nourishment of Manovaha Strotas: Array - Abdul Wakeel, Dr Saba Shaheen (Ayurline: International Journal of Research in Indian Medicine, 2019)
The prevalence of mental disorders is staggering, with 13.9% of adult Indians, suffering from a mental disorder in any given year. Psychiatric epidemiology has been an area of great interest among all the leading psychiatrists. From an Ayurvedic viewpoint, this vast morbidity reflects two things. Firstly: culture-wide deficiencies in diet and lifestyle are leading to impaired Agni, the root of either physical and mental health or disease,â€œLife-span, complexion, strength, health, enthusiasm, corpulence, luster, immunity, energy, etcâ€. All these depend on Agni.â€ Secondly, we inhabit a culture whose Rajasic and Tamasic nature is deleterious to our mental health. One of the unique features of Ayurveda is its emphasis on mental health through sattva. Right diet, right relationship, rituals, chanting and meditation form a comprehensive plan for preventative mental health.